Design of PID Controller using LQR-Based Parameter Selection for DC Motor Position Control - Hartono, Hartono; Budiarto, Eka; Nasution, Henry (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2025)
DC motors are widely applied in various fields due to their simple design, ease of control, and capability to generate high torque at low speeds. Position control of DC motors is crucial to ensure the performance and accuracy of the motorized electro-mechanical systems. The most common conventional control utilized in DC motors is the Proportional Integral Derivative (PID) controller. However, selecting the proper parameters for that controller is challenging. In this paper, the Linear Quadratic Regulator (LQR) approach is used to determine PID controller parameters for DC motors. The LQR approach, based on optimal control theory, offers a systematic alternative to traditional trial-and-error methods for tuning PID controllers. The proposed method improves the performance and efficiency of DC motors by optimizing the PID parameters, ensuring precise control and energy utilization.